Peningkatan Motivasi Belajar Melalui Pendekatan Penalaran Moral Menggunakan Aplikasi Games Educandy - Lince, Leny (Prosiding Seminar Nasional Fakultas Tarbiyah dan Ilmu Keguruan IAIM Sinjai, 2023)
The results of preliminary observations or preliminary studies conducted on the teaching and learning process in the classroom indicate that student learning activity is quite low. One indicator of the low learning activity is the low participation of students in learning activities. This indicator appears in the condition of students who tend to be passive, the courage to ask and answer questions is relatively lacking and the courage to express opinions on the problems being faced is also lacking. The results of interviews with teachers and experiences encountered, that at each meeting only 1-2 students dared to express their opinions or ask questions. As a result, it has an impact on learning motivation so that achievement is not achieved as expected. The purpose of this study is to describe the efforts of teachers in applying a moral reasoning approach to increase student motivation. Based on the results obtained in cycle I, the average score of learning outcomes was 87.3 from the ideal score that might be achieved, namely 100, the highest score achieved was 95 while the lowest score was 55. Based on the completeness standard, a score of 53% was obtained, namely 9 of 25 students belong to the complete category and 47%, namely 8 out of 25 students are included in the incomplete category, meaning that approximately half of the students need improvement In cycle II, the average score of student learning outcomes was 87.3 from the ideal score that might be achieved, namely 100, the highest score achieved was 95 while the lowest score was 55. The percentage of student completeness, namely 15 students or 88.2%, was included in the complete category and 2 people or 11.8% in the incomplete category. Based on the results of data analysis and the discussion described in the previous chapter, it can be concluded that the moral reasoning approach using game applications can improve students' abilities